2002
DOI: 10.1002/acp.842
|View full text |Cite
|
Sign up to set email alerts
|

The importance of being earnest: displayed emotions and witness credibility

Abstract: Participants viewed one of six video-recorded versions of a rape victim's testimony, role-played by a professional actress in one of six versions: Two versions of the testimony, representing a strong and a less strong rape scenario, were given in a free-recall manner with one of three kinds of emotions displayed, termed congruent, neutral and incongruent emotional expressions. Credibility judgements were strongly influenced by the emotions displayed, but not by the content of the story. When video watching was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
170
3
3

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 150 publications
(191 citation statements)
references
References 29 publications
15
170
3
3
Order By: Relevance
“…Confronted by an individual exhibiting an angry facial expression, one might wisely escape a dangerous encounter. In fact, emotional expressions are highly influential in determinations of mock witness testimony credibility, even more influential than the content of the testimony (Kaufmann, Drevland, Wessel, Overskeid, & Magnussen, 2003). However, the evolutionary development of deception and emotional concealment (which we think occurred later than rapid trustworthiness or dangerousness assessments in human evolution) has complicated the assessment of interpersonal trustworthiness (e.g.…”
Section: Dangerous Decisions In the Courtroommentioning
confidence: 92%
See 1 more Smart Citation
“…Confronted by an individual exhibiting an angry facial expression, one might wisely escape a dangerous encounter. In fact, emotional expressions are highly influential in determinations of mock witness testimony credibility, even more influential than the content of the testimony (Kaufmann, Drevland, Wessel, Overskeid, & Magnussen, 2003). However, the evolutionary development of deception and emotional concealment (which we think occurred later than rapid trustworthiness or dangerousness assessments in human evolution) has complicated the assessment of interpersonal trustworthiness (e.g.…”
Section: Dangerous Decisions In the Courtroommentioning
confidence: 92%
“…Although judges and jury members no doubt strive to maintain objectivity, they are not immune from normal human biases and may not be aware of the influences upon their decision-making (Kaufmann et al, 2003). Further, judges are susceptible to critical thinking errors and a reliance on false stereotypes that may be cited to justify their initial, unreliable assessment (e.g.…”
Section: Dangerous Decisions In the Courtroommentioning
confidence: 99%
“…Not only does emotional tone and content influence memory for testimony (Block et al, 2009), but credibility of victims varies as a function of emotional expression (Kaufman et al, 2003;Wessel et al, 2006). In general, research has reported that victims who display emotions (relative to appearing non-emotional) are often seen as more credible and not responsible for being victimized (e.g., Bollingmo, Wessel, Eilertsen, & Magnussen, 2008;Kaufmann et al, 2003). For example, Winkel and Koppelaar (1991) had participants watch either a video with an emotional (mock) rape victim, softly crying and relaying her story in a trembling voice, or a numb individual relaying her story without emotion.…”
Section: The Role Of Emotionmentioning
confidence: 99%
“…One such factor under investigation in the present study is the emotionality of a claim and whether this influences witness credibility. Past research has suggested that expressed emotion and emotional displays are highly relevant to consider in judicial decision-making (e.g., Block, Greenberg, & Goodman, 2009;Kaufmann, Drevland, Wessel, Overskeid, & Magnussen, 2003;Wessel, Drevland, Eilertsen, & Magnussen, 2006). Given this relationship, consideration of juror factors that may affect the interpretation of emotionality, such as the manner in which persons process information (i.e., rational versus emotional; Epstein, 2003) or the degree to which they have emotional processing deficiencies (i.e., psychopathy; Dutton, 2012) also is critical.…”
Section: Introductionmentioning
confidence: 99%
“…In the courtroom, a child may cry a little, cry hysterically, or not cry at all while providing their testimony. Kaufmann, Drevland, Wessel, Overskeid, and Magnussen (2003) have argued that jurors' credibility ratings are influenced more by the complainant's emotions and/or behaviours than by the facts contained in his or her testimony. For example, Regan and Baker (1998) asked participants to read a courtroom scenario of a 6-year-old girl who accused her father of sexual abuse.…”
Section: Discussionmentioning
confidence: 99%